2014
DOI: 10.1021/jp411096d
|View full text |Cite
|
Sign up to set email alerts
|

Melting of DNA Nonoriented Fibers: A Wide-Angle X-ray Diffraction Study

Abstract: The melting transition of A- and B-DNA has been investigated by wide-angle X-ray diffraction. A significant crystalline phase is present in both the systems, even if the fibers have not been artificially aligned. The behavior of the intramolecular Bragg peaks of both A- and B-DNA as a function of the temperature clearly reveals the unfolding structural transition of the double helix. This transition occurs at the same temperature as the melting of the crystalline phase. The trends of the intramolecular correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…It is likely that sample quality also plays a role. A recent study on non-oriented fibers showed very similar Bragg peak behaviour in both A-and B-DNA [6], with both data sets resembling our measurements on B-DNA [8]. It is feasible that the previous study also suffered from fiber collapse, hence explaining the similarity of the two data sets.…”
Section: Neutron Diffraction Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is likely that sample quality also plays a role. A recent study on non-oriented fibers showed very similar Bragg peak behaviour in both A-and B-DNA [6], with both data sets resembling our measurements on B-DNA [8]. It is feasible that the previous study also suffered from fiber collapse, hence explaining the similarity of the two data sets.…”
Section: Neutron Diffraction Resultssupporting
confidence: 84%
“…However, the DNA often takes a combination of A and B-forms, as well as molecules with B-A interfaces, so that experimental results cannot be quantitatively interpreted. A-DNA can be prepared from randomly oriented fibers and studies of the melting process have been reported [6]. Neither DNA in solution nor in randomly oriented fibers will give unambiguous experimental information on the spatial structure.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct result, we emphasized the importance of sequence length on the hysteresis phenomenon. This result is similar to previous published work [31,32], where the relevance of the sequence is key when studying DNA melting.…”
Section: Resultssupporting
confidence: 92%
“…The rise of the DNA melting temperature due to electrostatic interactions predicted in such a theoretical paper has just been proved experimentally [32].…”
Section: Temperature-driven Dna Denaturationmentioning
confidence: 80%
“…From a broader perspective on biological matter, it is interesting to compare the protein system to the well-studied example of DNA: analogously to the observations in our protein-cation systems, cation-82 and polymer- 83 induced attraction between DNA strands can similarly stabilise and shift the melting temperature of DNA to higher values. An additional factor influencing the melting transition of DNA is its degree of hydration, 84 which provides another conceptual link between phase transitions of DNA and proteins. The crucial aspect of hydration in our protein-cation systems will be discussed in more detail in the following.…”
Section: Discussionmentioning
confidence: 99%